Novel KLHL26 variant associated with a familial case of Ebstein’s anomaly and left ventricular noncompaction - Samudrala, Sai Suma K.; North, Lauren M.; Stamm, Karl D.; Earing, Michael G.; Frommelt, Michele A.; Willes, Richard; Tripathi, Swarnendu; Dsouza, Nikita R.; Zimmermann, Michael T.; Mahnke, Donna K.; Liang, Huan Ling; Lund, Michael; et al. (Molecular genetics & genomic medicine, 2020)
Background Ebstein's anomaly (EA) is a rare congenital heart disease of the tricuspid valve and right ventricle. Patients with EA often manifest with left ventricular noncompaction (LVNC), a cardiomyopathy. Despite implication of cardiac sarcomere genes in some cases, very little is understood regarding the genetic etiology of EA/LVNC. Our study describes a multigenerational family with at least 10 of 17 members affected by EA/LVNC. Methods We performed echocardiography on all family members and conducted exome sequencing of six individuals. After identifying candidate variants using two different bioinformatic strategies, we confirmed segregation with phenotype using Sanger sequencing. We investigated structural implications of candidate variants using protein prediction models. Results Exome sequencing analysis of four affected and two unaffected members identified a novel, rare, and damaging coding variant in the Kelch‐like family member 26 (KLHL26) gene located on chromosome 19 at position 237 of the protein (GRCh37). This variant region was confirmed by Sanger sequencing in the remaining family members. KLHL26 (c.709C > T p.R237C) segregates only with EA/LVNC‐affected individuals (FBAT p < .05). Investigating structural implications of the candidate variant using protein prediction models suggested that the KLHL26 variant disrupts electrostatic interactions when binding to part of the ubiquitin proteasome, specifically Cullin3 (CUL3), a component of E3 ubiquitin ligase. Conclusion In this familial case of EA/LVNC, we have identified a candidate gene variant, KLHL26 (p.R237C), which may have an important role in ubiquitin‐mediated protein degradation during cardiac development. Patient's Ebstein's anomaly (EA), a rare congenital heart disease of the tricuspid valve and right ventricle often manifest with left ventricular noncompaction (LVNC), a cardiomyopathy. Our study identifies a novel, rare, and damaging coding variant c.709C > T (p.R237C) in the Kelch‐like family member 26 (KLHL26) gene with 10 affected out of 17 affected members using Sanger sequencing. Through structural modeling, we show that the KLHL26 variant may affect protein binding to Cullin3 (CUL3), a component of E3 ubiquitin ligase in the ubiquitin‐mediated protein degradation.